The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.5539/ijbm.v10n3p108
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Leadership: The Effect on Employees

Abstract: Empirical evidence shows that the growing number of business excellence in the contemporary business environment is attributed to the leadership competencies. The frameworks of ethical leadership embody the need to engage the precincts of psychological empowerment with regard to influencing the organizational performance and the moral identity of employees. This study examines the influence that ethical leadership behavior has on the performance, efficiency and productivity of employees. Based on existing lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 17 publications
(25 reference statements)
0
29
0
5
Order By: Relevance
“…This study argues that Authentic Leadership have an important role in achieving good and lasting results, promoting organizational identity, emotional commitment and goal-oriented performance, as suggested by George and Zhou (2007). Researchers found out that there is a positive relationship between authentic leaders and employees (Alshammari, Almutairi, & Thuwaini, 2015), and it results in better creativity and performance of the employees (Karatepe & Aga, 2013). The result of the study show that authentic leadership affects the organizational identity, goal-oriented performance and emotional commitment of the employees positively.…”
Section: Discussionmentioning
confidence: 81%
“…This study argues that Authentic Leadership have an important role in achieving good and lasting results, promoting organizational identity, emotional commitment and goal-oriented performance, as suggested by George and Zhou (2007). Researchers found out that there is a positive relationship between authentic leaders and employees (Alshammari, Almutairi, & Thuwaini, 2015), and it results in better creativity and performance of the employees (Karatepe & Aga, 2013). The result of the study show that authentic leadership affects the organizational identity, goal-oriented performance and emotional commitment of the employees positively.…”
Section: Discussionmentioning
confidence: 81%
“…Peus, Wesche, Streicher, Braun, and Frey (2012) also supported the direct effect of AL on affective commitment. Both transformational and ethical leadership have also been confirmed to have a positive relationship with affective commitment (Allen & Meyer, 1996; Alshammari et al, 2015; Bass & Riggio, 2006; Meyer et al, 2002; Podsakoff, MacKenzie, & Bommer,1996; Rafferty & Griffin, 2004; Yucel, McMillan, & Richard, 2014).…”
Section: Research Background and Hypothesis Developmentmentioning
confidence: 94%
“…Previous research has found that AL enhances employees’ positive attitudes and behaviors (Avolio & Gardner, 2005; B. George, 2003; Ilies, Morgeson, & Nahrgang, 2005) and consequently their organization’s performance (Alshammari, Almutairi, & Thuwaini, 2015; Avolio & Mhatre, 2012; Walumbwa et al, 2008). Despite some overlap detected between AL and other leadership theories, AL has unique components, namely, self-awareness, balanced processing of information, internalized moral perspective, and relational transparency.…”
Section: Research Background and Hypothesis Developmentmentioning
confidence: 98%
“…According to Gomez, Balkin and Cardy cited in Alshammari et al (2015) argue that the distinctive pattern of ethical leadership is to embody and articulate organizational goals and values. Leaders in this context symbolize morals and narrate ethics to show the practical basis of ethical values.…”
Section: Literature Reviewmentioning
confidence: 99%